ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN TEMPAT TERHADAP PENJUALAN AIR MINUM ISI ULANG (STUDI DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU) - Admarita; Purwantoro (Program Studi Manajemen Universitas Pasir Pengaraian, 2020)
This study aims to determine the effect of product quality, price and temperature on the sale of refill drinking water in Rambah Hilir District, Rokan Hulu Regency. The population in this study are consumers who shop in Rambah Hilir District, Rokan Hulu Regency, with a total of 20 respondents. The sampling technique used is random sampling. The results showed that (1) the Product Quality variable did not have a significant effect. on the sales variable, which is stated by the t test in which the product quality variable that tcount <ttable, i.e. - 716 <1.745 (2) Price variable has a significant effect. on the sales variable, which is stated by the t test where the price variable is that the tcount> of the table, which is 6.576> 1.745 (3) the Place variable has no significant effect. against the Sales variable, which is stated by the t test where that the value of t <t table, that is -, 074 <1.745. Furthermore, (4) Together the three independent variables namely Product Quality, Price and Place affect Sales. This can be seen from the Test f shows the value of sig. of the three independent variables namely the variable Product Quality, Price and Place value of Fcount ˂ F table which is 0.400> 2.71.